L’écriture de l’autarcie dans Je t’offrirai une gazelle de Malek Haddad - ATOUI, Nour El Houda (Journal of Human Sciences, 2017)
Lucien Dällenbach distinguishes three types of intertextuality: the general intertextuality, the restricted intertextuality and the autarkic intertextuality (autotextuality).The autotextuality manifested by the “mise en abyme” present in Je t’offrirai une gazelle that includes an image in another image that reflects necessarily; so it becomes a relation of interlocking between a reflective story and a reflexive story. In this perspective, the overall story becomes a specular story that, by the mirror effect, reflects his own narrative principles.